'n Nota oor die vertaling van Jeremia 2:37 ("Met jou hande op jou hoof") - Stander, Hennie (Verbum et ecclesia, 1998)
A note on the translation of Jeremiah 2:37 ("With your hands on your head") In Jeremiah 2:37 God says to Israel: "You will leave that place (= Egypt) with your hands upon your head". In this article various Bible translations and commentaries are scrutinized to determine how modem exegetes interpret this phrase. Thereafter the author discusses Egyptian depictions of mourners in funeral processions with their hands on their heads. He shows how an exploration of Egyptian Art can contribute to a better understanding of Jeremiah 2:37. This study also shows that the two dynamic Afrikaans translations of the Bible ("Die Lewende Bybel" and "Die Nuwe Afrikaanse Vertaling") are wide off the mark in their interpretation of the phrase "with your hands on your head". The author also argues that exegetes should not only rely on written texts when they study the ancient world in which the Scriptures originated, but that they should also explore works of art.